2018
DOI: 10.1186/s12933-018-0783-z
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activity and hypercoagulation in type 2 diabetes

Abstract: BackgroundA strong correlation exists between type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD), with CVD and the presence of atherosclerosis being the prevailing cause of morbidity and mortality in diabetic populations. T2DM is accompanied by various coagulopathies, including anomalous clot formation or amyloid fibrin(ogen), the presence of dysregulated inflammatory molecules. Platelets are intimately involved in thrombus formation and particularly vulnerable to inflammatory cytokines.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 44 publications
4
76
0
3
Order By: Relevance
“…slips. This has also previously been noted in various publications (Page et al, 2018;Pretorius et al, 2018d;Page et al, 2019).…”
Section: Thromboelastography Cholesterol and Hba1c Levels And Ultrasupporting
confidence: 83%
“…slips. This has also previously been noted in various publications (Page et al, 2018;Pretorius et al, 2018d;Page et al, 2019).…”
Section: Thromboelastography Cholesterol and Hba1c Levels And Ultrasupporting
confidence: 83%
“…Thus, more evidence for the value of Fib in cardiovascular risk stratification in different subgroups were needed. and inflammatory processes in diabetes [22,29]. Impaired glucose metabolism and the status of insulin resistance result in oxidative stress, inflammatory response, coagulation activation, and accelerated atherosclerosis pathogenesis [30].…”
Section: Fib and Coronary Artery Diseasementioning
confidence: 99%
“…It was previously shown that thrombus and stents are adhesive due to the fibrin networks of the dense thrombus surface, determined by a range of initiators of thrombus formation [20]. Patients with diabetes mellitus show accelerated clot initiation caused by platelet activity and hypercoagulation, and adverse reaction milieu characteristics due to diabetes mellitus lead to a dysregulated clotting system [21,22]. In addition, diabetes mellitus indicates the formation of more compact fibrin networks in the thrombi [23], whilst red blood cells in the thrombi are mainly captured by fibrin networks during thrombi formation [24].…”
Section: Discussionmentioning
confidence: 99%